Osteoblast Demineralization Induced by Oxidized High-Density Lipoprotein via the Inflammatory Pathway Is Suppressed by Adiponectin - Noor Hanisa, Harun; Gabriele Ruth Anisah, Froemming; Aletza, Mohd Ismail; Hapizah, Nawawi; Siti Shuhada, Mokhtar; Suhaila, Abd Muid (MDPI, 2022)
Low mineralization activity by human osteoblast cells (HOBs) indicates abnormal bone remodeling that potentially leads to osteoporosis. Oxidation, the most prominent form of high-density lipoprotein (HDL) modification, is suggested to affect bone mineralization through the inflammatory pathway. Adiponectin, which possesses anti-inflammatory activity, is postulated to have the ability to suppress the detrimental effects of oxidized HDL (oxHDL). This study aimed to investigate the effects of HDL before and after oxidation on markers of mineralization and inflammation. The protective effects of adiponectin on demineralization and inflammation induced by oxHDL were also investigated. OxHDL at 100 µg/mL protein had the highest inhibitory effect on mineralization, followed by lower calcium incorporation. OxHDL also had significantly lower expression of a mineralization marker (COL1A2) and higher expression of inflammatory markers (IL-6, TNF-α, and RELA proto-oncogene, NF-κβ (p65)) compared to the unstimulated control group. These findings suggest that oxHDL reduces the mineralization activity of HOBs by increasing the expression of inflammatory markers. Interestingly, co-incubation of adiponectin and oxHDL in HOBs resulted in higher expression of mineralization markers (ALPL, COL1A2, BGLAP, and RUNX2) and significantly reduced all targeted inflammatory markers compared to the oxHDL groups. On the contrary, HDL increased the expression of mineralization markers (COL1A2 and STAT-3) and exhibited lower expression of inflammatory cytokines (IL-6 and TNF-α), proving the protective effect of HDL beyond the reverse cholesterol transport activity.